Coming Home or Drifting Away: Magical Practice in the Twenty-First Century—Ways of Adopting Heterodox Beliefs and Religious Worldviews - Mayer, Gerhard (Journal of contemporary religion, 2010)
This article examines the process-related dynamics of becoming a magical practitioner and an adherent of a Neopagan group, respectively. It analyzes the relation of the thesis of Interpretive Drift (Luhrmann) and the concept of Coming Home Experience, which have a big impact on academic discussions and are often seen as mutually contradictory. Using empirical data from two German interview studies with contemporary magicians and German heathen (Ásatrú) groups, the article shows that the two dynamics can form complementary elements of the process. In addition, it emphasizes the importance of personal extraordinary experiences containing strong subjective evidence which are mostly neglected. Taking individual biographical aspects into account as well as different personal motivations, an immense variety of approaches to alternative worldviews might become possible. Thus we come to the conclusion that simple generalizations in characterizing the pathway to magical beliefs and practices' are misleading.